Problems in managing foreign bodies in the upper aerodigestive tract (Medical Journal of Indonesia, 2002)
The incidence of foreign body aspiration and ingestion in esophagus is higher in children under five years old. Especially for young children, suffocation from inhalation and ingestion of foreign bodies represents the highest cause of home accidental death. To some extent, establishing the diagnosis of foreign body ingestion or aspiration remains a big problem due to some difficulties in taking the history, getting the accurate signs and symptoms and performing radiologic examination. Therefore, beside the availability of the necessary equipments, the management of these particular cases requires person with expertise and professional skill in endoscopy. This paper will discuss several problems happening to real patients in the case of aspirated plastic materials and peanut as well as stones and dentures that were stuck in the esophagus. (Med J Indones 2002; 11: 15-8)Keywords: foreign body, esophagoscopy, bronchoscopy